Relationship between lymph nodes examined and survival benefits with postoperative radiotherapy in oral cavity squamous cell carcinoma patients with stage T1-2N1M0 - Fan, Sufeng; Jiang, Wenmei; Fang, Zhongyi; Li, Ruiyu; Li, Yudong; Chen, Yanfeng; Zhang, Quan (Frontiers in Surgery, 2022)
Background This study aims to explore the relationship between the lymph nodes examined and survival benefits of postoperative radiotherapy in oral cavity squamous cell carcinoma patients with stage T1-2N1M0. Methods This study retrieved patients who underwent dissection of the primary site and neck lymph nodes for pT1-2N1M0 oral cavity squamous cell carcinoma without adverse nodal features from the Surveillance, Epidemiology, and End Results database from 2004 to 2015. Propensity score matching analysis was conducted, and the best cutoff value of the lymph nodes examined was determined by X-tile. Cancer-specific survival was the primary outcome. Univariable and multivariable analyses were performed to assess the relation between postoperative radiotherapy and cancer-specific survival, adjusting for other prognostic factors. Results A total of 469 patients were finally enrolled according to our exclusion criteria, and then 119 pairs of patients were matched by propensity score matching analysis. The best cutoff value of the lymph nodes examined was determined by X-tile, stratifying patients into lymph nodes examined ≤16 group and lymph nodes examined >16 group. For the whole matched cohort, the choice of postoperative radiotherapy had no correlation with other factors (all p’s > 0.05), and postoperative radiotherapy made no contribution to a better survival outcome for patients (p = 0.289). After stratified by the lymph nodes examined, in the lymph nodes examined ≤16 group, significantly improved CSS was found for those who undertook postoperative radiotherapy compared to those who just received surgery (unadjusted hazard ratio, 0.541; 95% confidence interval, 0.333–0.878; p = 0.013). Conclusions Our study revealed that pT1-2N1M0 oral cavity squamous cell carcinoma patients were more likely to benefit from postoperative radiotherapy when unsatisfactory neck dissection was conducted, indicating that the number of lymph nodes examined might be a factor when clinicians do therapeutic planning for early-stage oral cavity squamous cell carcinoma patients.